Sistem Informasi Gereja terpadu berbasis web dengan framework CodeIgniter 4 - Norotama, Unggul Prabowo; Chernovita, Hanna Prillysca (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2026)
This study focuses on development of a web-based information system for Father House Community Church (FHCC) in Salatiga, using the CodeIgniter 4 framework. The system is designed to support the digital management of church activities, including congregation data management, dissemination of church information, cell group (iCare) mapping, and the provision of daily devotionals in a digital format. The research applies a system development approach based on the Model-View-Controller (MVC) architecture, which separates the application logic, data management, and user interface to improve system development efficiency. The system development includes requirements analysis, system design, implementation, and testing to ensure that the application meets the needs of users. The results show that the developed system effectively improves the efficiency and accuracy of congregation data management while facilitating better communication between the church administration and its members. Moreover, the web-based platform allows users to access church information and services in real time through a browser without requiring additional software installation, thereby improving accessibility, usability, and overall service quality.